Estudios científicos sobre el agua en el Boletín de la Sociedad Mexicana de Geografía y Estadística, 1857-1869 (Estudios) - Vega y Ortega Baez, Rodrigo A. (2019)
Research on the country’s water resources was published in the Bulletin of the Mexican Geography and Statistics Association (Boletín de la Sociedad Mexicana de Geografía y Estadística). This article identifies the issues about water prevailing in this publication: water resources, hydraulic infrastructure projects, and their use in the city. These three issues highlight the concerns of geographers, physicians, engineers, and naturalists who recognized the value of water for the country’s economic, demographic, and social future, in addition to the difficulties of securing clean water and infrastructure projects to tackle environmental problems.